Autoimmune sensorineural hearing loss/Meniere’s disease possibly triggered by neurocysticercosis: a case report - Hamza Arman Lateef; Evan Davies; Alidad Arabshahi (Journal of Medical Case Reports)
Abstract Background Meniere’s disease arises when an abnormal fluid accumulation results in heightened pressure within the inner ear or labyrinth. Its symptoms encompass vertigo, tinnitus, hearing loss, and a sensation of fullness in the ear. Various triggers for Meniere’s disease are known, from smoking and alcohol consumption to recent viral illnesses, allergies, and anxiety. Meniere’s disease presenting as a postinfectious inflammatory condition secondary to parasitic disease is unknown. Case presentation A 37-year-old Hispanic male patient, native to southern Honduras, presented with dizziness and tinnitus. These symptoms progressed to include left-sided sensorineural hearing loss. The patient was clinically diagnosed with Meniere’s disease and referred to an otolaryngologist. Laboratory work-up revealed a positive result for the anti-heat shock proteins antibody and abnormal electrocochleography, more prominent on the left than the right. His vestibulonystagmogram displayed both central and peripheral findings, and bithermal caloric irrigations suggested abnormal peripheral function with a 57% weakness in the left ear. Despite dietary and lifestyle modifications, as well as treatment with oral steroids, his symptoms persisted. More detailed history revealed that he had been treated for a tapeworm infection at the age of 14 years in his Honduran village. Subsequent magnetic resonance imaging scans of the brain highlighted postinflammatory calcification in the right parietal lobe and generalized volume loss, more substantial than what would be expected for the patient’s age. The patient was also referred to rheumatology and neurology, where he was diagnosed with neurocysticercosis. Conclusion To the authors’ knowledge, this is the first report suggesting that Meniere’s disease could be possibly triggered by or concurrent with neurocysticercosis. This highlights the need for a comprehensive examination to identify any coexisting neurological conditions in patients presenting with Meniere’s disease.